Relaxation of active acoustic emission sources during the natural aging of A³B⁵ epitaxial structures - Veleschuk, V.P.; Lyashenko, O.V. (Functional Materials, 2004)
The aging processes of A³B⁵ epitaxial light-emitting structures have been shown to reduce acoustic emission (AE) intensity, AE count, and to raise the AE onset threshold while an increased change rate of the direct current through junction results in that AE onset threshold becomes shifted towards lower currents, the failure currents drop, and AE intensity and AE count increase. Показано, что процессы старения эпитаксиальных светоизлучающих структур на основе соединений A³B⁵ уменьшают интенсивность акустической эмиссии (АЭ), суммарную АЭ и повышают порог возникновения АЭ, а увеличение скорости изменения постоянного электрического тока через переход — к смещению порога возникновения АЭ в область меньших токов, уменьшению токов разрушения, а также возрастанию интенсивности АЭ и суммарной эмиссии. Показано, що процеси старіння епітаксійних світловипромінювяльних структур на основі сполук A³B⁵ зменшують інтенсивність акустичної емісії (АЄ), сумарну АЄ та підвищують поріг виникнення АЄ, а збільшення швидкості зміни постійного електричного струму через перехід — до зміщення порогу виникнення АЄ в область менших струмів, зменшення струмів руйнування, зростання сумарної емісії та інтенсивності АЄ.